Pelatihan Ecoprint Daun Mangrove untuk Peningkatan Ekonomi Kreatif Masyarakat Lokal Papua di Pantai Payum Merauke - Sajriawati Sajriawati; Reny Sianturi; Nurliah Nurliah; Sunarni Sunarni (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Mangrove leaf ecoprint training was held at Payum Beach, Merauke, South Papua, with the aim of empowering local communities through the development of a mangrove-based creative economy. This activity introduced the ecoprint technique as a natural dyeing method on fabrics using pigments and shapes from diverse mangrove leaves in the area. Active community participation in this training is expected to improve their skills in producing unique and marketable ecoprint products. Furthermore, this initiative has the potential to open up new business opportunities, utilize mangrove natural resources sustainably, and preserve traditional knowledge related to local plants. Post-training evaluations showed enthusiasm and increased understanding of participants towards the ecoprint technique, indicating the significant potential of mangrove leaf ecoprint in stimulating the growth of the creative economy in the coastal communities of Merauke.